Interactions between Dental MSCs and Biomimetic Composite Scaffold during Bone Remodeling Followed by In Vivo Real-Time Bioimaging - Costa, AC (2023)
Oral–maxillofacial tumor removal can generate critical bone defects and major problems for patients, causing dysfunctionalities and affecting oral competencies such as mastication, swallowing, and breathing. The association of novel biomaterials and cell therapies in tissue engineering strategies could offer new strategies to promote osteomucosa healing. This study focused on the development of a bioengineered construct loaded with human dental follicle cells (MSCs). To increase the bioconstruct integration to the surrounding tissue, a novel and comprehensive approach was designed combining an injectable biomimetic hydrogel and dental stem cells (hDFMSCs) expressing luminescence/fluorescence for semi-quantitative tissue imaging in live animals. This in vivo model with human MSCs was based on an intramembranous bone regeneration process (IMO). Biologically, the biocomposite based on collagen/nanohydroxyapatite filled with cell-loaded osteopontin–fibrin hydrogel (Coll/nanoHA OPN-Fb) exhibited a high cellular proliferation rate, increased bone extracellular matrix deposition (osteopontin) and high ALP activity, indicating an early osteogenic differentiation. Thus, the presence of human OPN enhanced hDFMSC adhesion, migration, and spatial distribution within the 3D matrix. The developed 3D bioconstruct provided the necessary pro-regenerative effect to modulate the biological response, precisely fitting the bone defect with fine-tuned adjustment to the surrounding original structure and promoting oral osteomucosa tissue regeneration. We were also able to track the cells in vivo and evaluate their behavior (migration, proliferation, and differentiation), providing a glimpse into bone regeneration and helping in the optimization of patient-specific therapies.